Genetic divergence among castor bean lines and parental strains using ward’s method based on morpho-agronomic descriptors - Silva, Adielle Rodrigues da; Silva, Simone Alves; Santos, Laurenice Araújo; Souza, Deoclides Ricardo de; Araújo, Gilmara de Melo; Moreira, Ricardo Franco Cunha (Acta Scientiarum. Agronomy, 2017)
This study sought to evaluate the genetic divergence among castor lines and parental strains in the germplasm bank at the Federal University of Recôncavo da Bahia (Universidade Federal do Recôncavo da Bahia) using morpho-agronomic descriptors. This experiment was conducted from 2014 to 2015 with 208 treatments represented by bank accessions that were analyzed using a randomized block design, which established homogeneity of the experimental conditions with all treatments repeated in four blocks. The genetic divergence analysis was performed using Ward’s method and Tocher’s method based on Gower’s distance, which are two clustering methods used in studies with castor beans, with the help of the statistical programs R and GENES. The results revealed the formation of 21 groups for 13 morpho-agronomic descriptors, six qualitative and seven quantitative, indicating the presence of variability in the bank. The groups containing promising accessions for the characteristics of agronomic interest, including precociousness, fruit dehiscence, and plant height and yield were 2, 7, 8, 10, 14, 15, 16, and 17, which suggested potential hybrid crosses. The descriptors with the greatest contribution to variance were yield, plant height, the number of seeds per raceme, flowering and seed weight per raceme.